Assessing the need for routine safety testing for patients being treated with dupilumab for moderate‐to‐severe atopic dermatitis. (1st June 2020) - Wollenberg, A; Beck, L.A.; Blauvelt, A.; Simpson, E.L.; Chen, Z.; Chen, Q.; Shumel, B.; Khokhar, F.A.; Hultsch, T.; Rizova, E.; Rossi, A.B.; Graham, N.M.H.; et al.
Summary: Atopic dermatitis (also known as AD or eczema) is a common skin disease that can cause intense and persistent itching and rashes. Skin creams or ointments are not suitable or effective for some patients with moderate‐to‐severe AD. In these patients, oral (taken by mouth) or injected medications may be required. Some of those oral or injected treatments could be toxic and often have unwanted side effects, especially when used for a longer period of time, so patients must be regularly tested to see whether those treatments are harming their blood or organs. Dupilumab is a newer injectable drug for treating moderate‐to‐severe AD. Dupilumab specifically targets key molecules in the body that cause AD. Dupilumab has been tested for up to one year in more than 2000 patients enroled in placebo‐controlled clinical trials. During those trials, patients provided blood and urine samples for laboratory testing while they were being treated with dupilumab or placebo (dummy drug). In this paper, the authors from Germany and the U.S.A, analysed how blood cells, blood chemistry, and urine chemistry changed during treatment, to check whether dupilumab is safe to use without the need for regular laboratory tests. After performing many routine laboratory tests on patients' blood and urine, they found that there were no clinically important changes in test results that could be linked to dupilumab. They concluded that patients using dupilumab for moderate‐to‐severe AD do not need routine laboratory testing. This is a summary of the study: Laboratory safety of dupilumab in moderate‐to‐severe atopic dermatitis: results from three phase III trials (LIBERTY AD SOLO 1, LIBERTY AD SOLO 2, LIBERTY AD CHRONOS)